Pengaruh Bauran Pemasaran (7p) terhadap Keputusan Pembelian Motor Yamaha Tipe Nmax - Samron Akhiri (Management Studies and Entrepreneurship Journal (MSEJ), 2019)
The purpose of the research to determine the effect of marketing mix (7p) Buying Decision Against Type Nmax At Yamaha Motor PD. Panca Motor Prabumulih This type of research is the method used in this research is survey method. Data collected consist of primary data and secondary data. The primary data obtained through interviews method which is equipped with a questionnaire has been prepared. In this study the number of population is not known, therefore, that according to Widiyanto in Vina Agustina (2012: 56) to determine the sample size of the population can use the formula. So a sample to be used is a total of 96 customers in PD. Panca Motor Prabumulih. Respondent data collected by collecting primary data, which collects data by distributing questionnaires were collected by questionnaire purchasing decisions. Data was analyzed using correlation and regression analysis. The results showed that, of the model output obtained summary table of test results gives the coefficient of determination R Square of 0.744. This shows that the variable marketing mix (product, price, distribution, promotion, people, process and physical environment) simultaneously percentage contribution of the influence of independent variables have an influence on the dependent variable (Decision consumers to shop), amounting to 74.4%. Or the independent variable (product, price, distribution, promotion of people, processes and physical environment) amounted to 74.4% were able to explain the dependent variable (Decision consumers to shop), while the remaining 25.6% influenced or explained by other variables not examined in this research. Keywords: Marketing Mix (7P), Purchase Decision